Out of Africa - Bošković, Aleksandar (Etnolog. Nova vrsta (Ljubljana), 2001)
The article explores images of sub-Saharan African women. These images can be seen as the sign of the times and markers of the colonial expansion, as well as powerful signs of the colonizersć own insecurities and feelings of lack (especially when it comes to sexuality). Through these representations, one can see how perceptions are also changing - more recently, into the images where women are increasingly depicted as independent, outspoken, and strong. While these images are still competing with the more antiquated ones, the new iconography will undoubtedly influence generations of young women (as well as men) that are increasingly questioning the old stereotypes.
Keywords: woman; ženske; položaj žensk; antropologija spola; Africa; Afrika